2022
DOI: 10.1002/mp.15693
|View full text |Cite
|
Sign up to set email alerts
|

Accurate dose measurements using Cherenkov emission polarization imaging

Abstract: Purpose Cherenkov radiation carries the potential of direct in‐water dose measurements, but its precision is currently limited by a strong anisotropy. Taking advantage of polarization imaging, this work proposes a new approach for high‐accuracy Cherenkov emission dose measurements. Methods Cherenkov radiation produced in a 15 × 15 × 20‐cm3 water tank is imaged with a cooled charge‐coupled device (CCD) camera from four polarizer transmission axes [0, 45, 90, 135°]. The water tank is positioned at the isocenter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The resulting images correspond to the Cherenkov signal summed over the water tank thickness along the optical axis. As a result, projected dose distributions are measured 18 . For each set of measurements, projected percent depth dose (PPDD) and projected profiles at depth of maximum dose ( ) were extracted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting images correspond to the Cherenkov signal summed over the water tank thickness along the optical axis. As a result, projected dose distributions are measured 18 . For each set of measurements, projected percent depth dose (PPDD) and projected profiles at depth of maximum dose ( ) were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Given the intrinsic polarization of Cherenkov emission, polarization imaging has potential benefits for dose measurements in radiotherapy that have not yet been exploited. Recently, a letter was published that presented promising results when using polarization imaging to correct the Cherenkov emission anisotropy which enabled accurate dose measurements 18 . The method takes advantage of polarization imaging to isolate the polarized contribution of the Cherenkov signal.…”
Section: Introductionmentioning
confidence: 99%
“…Cherenkov light is often considered as a parasite signal in light-based dosimetry such as with scintillators [1] but it has been recently demonstrated that it can be used as the primary signal for dosimetry using polarized imaging [2,3]. Cherenkov dosimetry has several benefits, one of which making real-time radiation treatment dosimetry possible [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cherenkov light is polarized by nature, however, the Cherenkov signal produced in a water phantom and captured by a camera is not entirely polarized due to scattering. To correct this, Cloutier et al developed a method based on the Malus law (𝐼 = 𝐼 𝑝𝑜𝑙 (cos(𝛼 0 − 𝛼)) 2 + 𝐼 𝑟𝑎𝑛𝑑.𝑝𝑜𝑙 ) [5] and Monte Carlo simulations to extract the polarized portion of the light (𝐼 𝑝𝑜𝑙 ) captured by a camera and calculate angular correction distributions to have a signal proportional to dose [2]. Such distributions account for Cherenkov photon loss due to photon interactions with the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation